Arabic as a Second Language: A Case Study on Expatriates in KSA - Talat Zahir Qamry (Talenta Publisher, 2022)
The present paper describes how expatriates of different linguistic backgrounds cope with the Arabic language differently during their stay in the Kingdom of Saudi Arabia. Linguistically, the expatriates here can be divided into two distinct categories; (1) those, for whom Arabic is not a foreign language; (2) those, for whom Arabic is a foreign language. The study analyzes the functional level of the Arabic language in category 2. Multiple sociolinguistic factors are responsible for learning or acquiring Arabic as an ASL, AFL, ALF, or ALL amongst the non-Arabic expatriates in KSA. The paper describes how the incomplete/ partial linguistic competency among the expatriates sometimes extended into a full-fledged skill- in the case of (A) those who stayed here longer for generations and could not return to their native place. (B) Those who go back to the native site forever as their job tenure is over. In both cases, language loss occurs; In terms of the case (A) First language loss is observed, on the other hand, in case (B) incomplete or partial (Arabic) language competency is lost. The persisting situation demands realistic affirmative action collectively.